The sleep, recovery, and nutrition characteristics of elite adolescent athletes - Mason, L.; Connolly, J.; Devenney, L. E.; Lacey, K.; O`Donovan, J.; Faulkner, M.; Doherty, R. (Sports, 2025)
Background: Elite sport participation creates a significant burden on adolescent athletes due to demanding training schedules, high training intensities, and the complexity of puberty. As such, an athletes` ability to effectively balance stress and recovery is essential for their athletic performance and requires appropriate management throughout the competitive season. This research aimed to investigate: (i) the quantity, quality, and timing of sleep; (ii) general and sport-specific nutrition knowledge; (iii) recovery practices; and (iv) the relationships between sleep, nutrition, and recovery practices in elite adolescent athletes.